ANALYSIS AND STRATEGY TO INCREASE THE INCOME OF TRADITIONAL SALAM NET FISHERMAN IN CENTRAL TAPANULI - Harahap, Mutiara Alkayakni; Harjuni, Fiki; Audina, Nur (Asian Journal of Aquatic Sciences, 2024)
Central Tapanuli Regency, Andam Dewi District, is an area that has a large water potential area. In this area, many fishing activities are carried out. Based on data on the number of fishermen in the Central Tapanuli area, the number of traditional fishermen in the Andam Dewi area is 1510 fishermen, and the type of fishing gear often used is the salam net. Dependence on using laurel net fishing equipment does not guarantee that fishermen get abundant catches and stable economic income. This research used purposive sampling using 35 salam fishing nets. This research aims to determine the level of welfare of fishermen based on the five livelihood capital approaches, namely natural capital, human capital, physical capital, financial capital, and social capital. The results of this research show the ability of fishermen to access fishing areas in the waters using 23% natural capital, 32% human capital, 18% physical capital, 9% financial capital, and 18% social capital